핸드메이드 마켓의 새로운 패러다임 -엣시(Etsy.com)를 중심으로 - 나유리; Na Yu Ri (기초조형학연구, 2017)
디지털 시대에서, 전형적인 아날로그의 상징인 `핸드메이드`가 재평가되고 있다. 그 현상의 주축에는 미국의 전통적 DIY 문화를 기반으로 성장한 온라인 핸드메이드 마켓, `엣시(Etsy.com)`가 있다. 본 논문은 미국 내 공예(문화적 현상의 역사적 배경을 바탕으로, 전임(前任)과 구별되는 엣시의 특성을 고찰하고, 엣시가 시사하고 있는 가치와 사회(문화적 파급 현상을 통하여 새로운 패러다임을 분석하는 것을 목표로 하였다. 본고는 엣시의 창립과 성장 배경을 미술공예운동과 DIY 운동, 펑크 하위문화, 페미니즘 운동과의 중심 철학과 내용적 연관성에서 찾으며, 미국 내 사회(문화적 변화의 움직임에 주목하였다. 엣시를 주축으로 나타나는 새로운 패러다임을 분석하기 위하여, 본 연구는 엣시의 내적 특질과 외적 특질로 나누어 조사하였다. 전자는 온라인 마켓인 엣시의 본질적 속성에 관한 연구로, 미국 내 인디 공예운동의 흐름 속에서 엣시의 창립 배경과 엣시의 출현의 의의를 DIY 문화의 연장선에서 고찰하며, 웹 2.0을 기반의 핸드메이드 마켓으로서의 특징을 살펴보았다. 분석의 결과로, 기존의 마켓과 차별된 엣시의 특성은 1) 사용자 친화적인 글로벌 마켓, 2) 사람과 사람을 연결하는 마켓, 3) 개인화된 소비자의 요구를 충족시켜 주는 마켓, 4) 커뮤니티 기반의 마켓으로 정리된다. 후자는 미국의 사회(문화적 풍토에 초점을 맞추며, 엣시를 중심으로 파생된 제작자 및 공예 문화의 현상을 5) 엣시를 통하여 출현한 새로운 제작자의 특성을 중심으로, 6) 이데올로기적 노동 운동과 7) 액티비즘의 관점에서 분석하고, 8) 소비문화를 대안적 소비의 관점에서 분석하여, 새로운 패러다임의 근거로 제시하였다. 엣시의 단편적 면모만을 다룬 기존의 연구들과는 달리, 본 논문은 장기간의 관찰을 통하여 엣시의 발전 및 엣시 주변의 사회(문화 현상을 설명하였으며, 파급된 긍정적인 사회(문화적 연계 현상을 새로운 패러다임에 포함하였다. In the digital era, `handmade`, typically an analog symbol, is being reevaluated. In the center of the phenomenon is `Etsy(Etsy.com)`, an online handmade market that has grown from the traditional DIY culture of the U.S. Based on the historical background of the cultural craft phenomenon in the U.S., this research aimed to examine a new paradigm through the socio-cultural diffusion of the phenomenon and values suggested by Etsy, as well as the essence of Etsy as distinguished from its predecessors. Finding the central philosophy of, and the contextual relationship with, the Arts & Crafts movement, the DIY movement, punk subculture, and the feminist movement, this study paid attention to socio-cultural change in the U.S. In order to analyze the new paradigm, this paper divided and analyzed the internal qualities and external qualities of Etsy. The former, a study of the essential attributes of Etsy as an online marketplace, examining the background of Etsy`s founding from the flow of the indie craft movement in the U.S., and Etsy`s emergence and significance as an extension of DIY culture, explored Etsy`s peculiarities as a handmade market in a Web 2.0 world. As a result of the analysis, the main features that differ from other markets are summarized as 1) a user-friendly global market, 2) connecting people, and 3) meeting the needs of personalized consumers 4) based on communities. The external qualities presented evidence of the new paradigm focusing on the socio-cultural climate in the U.S. It examined the phenomenon of makers and craft culture derived from Etsy 5) focusing on the characteristics of new makers emerging through Etsy 6) from the perspective of an ideological work movement, 7) of activism, and 8) of alternative consumption for consumer culture. Unlike other research dealing with some fragmentary aspects of Etsy, this study investigated Etsy`s development and the socio-cultural phenomenon around Etsy through long-term observation, and included positive socio-cultural linkages as the new paradigm.